2017
DOI: 10.1155/2017/2180508
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab for Treatment of Membranoproliferative Glomerulonephritis and C3 Glomerulopathies

Abstract: Membranoproliferative glomerulonephritis (MPGN) is a histological pattern of injury resulting from predominantly subendothelial and mesangial deposition of immunoglobulins or complement factors with subsequent inflammation and proliferation particularly of the glomerular basement membrane. Recent classification of MPGN is based on pathogenesis dividing MPGN into immunoglobulin-associated MPGN and complement-mediated C3 glomerulonephritis (C3GN) and dense deposit disease (DDD). Current guidelines suggest treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 54 publications
2
20
0
5
Order By: Relevance
“…Only one patient with DDD and positive C3Nef treated solely with rituximab showed stable renal function and improvement of nephrotic syndrome after 30 months of follow-up, but C3Nef remained positive and C3 levels were always low [73]. In contrast, other cases with DDD and C3G initially treated with rituximab achieved partial or complete remission on eculizumab [72,74].…”
Section: Treatment In C3 Glomerulopathymentioning
confidence: 93%
See 2 more Smart Citations
“…Only one patient with DDD and positive C3Nef treated solely with rituximab showed stable renal function and improvement of nephrotic syndrome after 30 months of follow-up, but C3Nef remained positive and C3 levels were always low [73]. In contrast, other cases with DDD and C3G initially treated with rituximab achieved partial or complete remission on eculizumab [72,74].…”
Section: Treatment In C3 Glomerulopathymentioning
confidence: 93%
“…Other studies have suggested some benefit from the use of cyclophosphamide, mycophenolate mofetil and a combination of aspirin and dipyridamole. Current guidelines suggest treatment with steroids and cytotoxic agents, with or without plasmapheresis, only in patients with progressive disease with nephrotic range proteinuria and a decline of renal function [72]. Because C3G is a new diagnostic category, long-term data on renal transplants are lacking, but recurrence is probably as high as in idiopathic MPGN type I (up to 65% in some series).…”
Section: Treatment In C3 Glomerulopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence or de novo C3 GP may receive other therapies that are under trough evaluation as (i) compostatin that is a C3 inhibitory peptide; (ii) CP40 is a compostatin analog [70]; (iii) monoclonal antibodies against C3b [71], FB [72] and properdin [73]. Moreover, soluble complement receptor 1(CR1)) may prevent the dysregulated alternative pathway caused by abnormal production of C3 convertase.…”
Section: Recurrence or De Novo C3 Gp After Kidney Transplatationmentioning
confidence: 99%
“…Patients with nephrotic syndrome and a decline in renal function should receive oral CYC or MMF plus a low dose of daily or alternate-day corticosteroids [33]. If despite this treatment nephrotic syndrome persists or the renal function impairs, tacrolimus or RTX can be considered although the percentage of its beneficial effect is very low [35,70].…”
Section: Therapymentioning
confidence: 99%